Consulting virtue: from judgement to decision‐making in the natural gas industry. (12th March 2019) - Mason, Arthur
Abstract: Shifts in the terrain of energy politics have given rise to consultant experts who produce and distribute knowledge of energy futures. Drawing on fieldwork at executive roundtables in global cities across North America, this essay examines the consolidation of this form of expertise and the opulent settings in which it is distributed. By exploring the role of aesthetic judgement in market‐orientated decision‐making, it contributes to anthropological work on elites, expertise, and energy ethics by highlighting the relationship between credibility and luxury. The essay also considers the enrolment of the expert in a kind of virtue ethics, whereby adherence to neoclassical economic principles is taken to be a character trait worthy of emulation. While clients may not look to consultants for advice coded in terms of ethics, I argue that they regard the person‐based qualities of consultants as proxies for their ability to recommend a judicious course of action. By adopting this analytic, the essay sheds new light on the confidence that clients place in consultants by drawing out the relationship between depersonalized, quantitative approaches to energy markets and the virtue of the persons who propose them.